Pengaruh Akupressure Dalam Menurunkan Nyeri Osteoarthritis Genu Pada Wanita Usia Premenopause - Aprilia Sri Rachmawati; Winarni Winarni (Lembaga Pengembangan Kinerja Dosen, 2023)
Background: The results of an interview with Dr. Gunawan Leonard, the incidence of OA Genu is often complained of by female patients at the Primary Metro Pundu clinic. This is due to long working hours and hard work. Management from the clinic still uses pain relievers such as ibuprofen. Long-term use of this drug will cause side effects on the body. To minimize these side effects, the researchers carried out non-pharmacological treatment with acupressure at the ST 36, ST 35, EX-LE 2, EX-LE 4, and BL 40 points in reducing OA pain. Objective: To determine the difference before and after being given acupressure in reducing OA pain in perimenopausal women. Method: This type of research is quantitative. The population of this study were all women of perimenopausal age who had osteoarthritis genu at the Metro Pundu Primary Clinic, Central Kalimantan, as many as 32 people. The number of samples used Freder's formula was 20 samples, and data processing used Shapiro Wilk for the normality test to obtain normally distributed data results and paired sample t test with the results of ha accepted. Results: There was a decrease in OA pain scale in perimenopausal women before and after being given acupressure treatment, This shows the effect of acupressure in reducing genu osteoarthritis pain in perimenopausal women.